Perlindungan Komunitas Lesbian, Gay, Biseksual dan Transgender (LGBT) di Kampus: Hukum HAM dan Kebebasan Akademik - Rohman Hidayad (Jurist-Diction, 2022)
AbstractIndonesia is a state of law and a country that upholds human rights. Although in the constitution there are no rules that specifically regulate the LGBT group. This thesis discusses the protection of the LGBT community on campus in terms of the legal system, human rights and the principles of academic freedom and how the state is responsible for fulfilling the rights of citizens, especially for LGBT groups on campus. The type of research used is the type of legal research with a conceptual approach and legislation in the perspective of human rights. This study shows that cases that occur in LGBT groups in Indonesia, especially in the campus environment, still receive less attention from the government. Cases that occur should make learning so that it does not happen again. In comparison to getting justice for LGBT people whose rights have been violated and discriminated against, there are several legal remedies by LGBT groups in the United States and Malaysia.Keywords: LGBT Groups; LGBT Groups on Campus; Legal Efforts for LGBT Groups. AbstrakIndonesia merupakan negara hukum dan negara yang menjunjung tinggi hak asasi manusia. Meskipun dalam konstitusi tidak ada aturan yang secara spesifik mengatur mengenai kelompok LGBT. skripsi ini membahas mengenai perlindungan komunitas LGBT di kampus di tinjau dari sistem hukum, HAM dan prinsip-prinsip kebebasan akademik serta bagaimana tanggungjawab negara dalam hal pemenuhan hak warga negara khususnya bagi kelompok LGBT di kampus. Tipe penelitian yang digunakan adalah tipe penelitian hukum dengan pendekatan konseptual dan dan perundang-undangan dalam sudut pandang hak asasi manusia. Penelitian ini menunjukkan bahwa kasus yang terjadi pada kelompok LGBT di Indonesia khususnya dalam lingkungan kampus masih kurang mendapatkan perhatian dari pemerintah. Kasus yang terjadi seharusnya menjadikan pembelajaran agar tidak tejadi lagi. Sebagai perbandingan untuk mendapatkan keadilan bagi kelompok LGBT yang haknya dilanggar dan mendapatkan diskriminasi, terdapat beberapa upaya hukum yang dilakukan kelompok LGBT di Amerika Serikat dan Malaysia.Kata Kunci: Kelompok LGBT; Kelompok LGBT di Kampus; Upaya Hukum Kelompok LGBT.